Determinants of Pregnant Women’s Compliance with the Triple Elimination Programme in Bandung City, Indonesia - Reynie Purnama Raya; Santi Nur Holizah; Bhekti Imansari (Journal of Public Health Sciences, 2026)
The Triple Elimination Programme was first introduced in 2017 to standardise screening for pregnant women nationwide. Moving into 2025, however, coverage rates in several regions—including Bandung City—remain below national targets, pointing to an ongoing struggle with programme compliance. This study examined the association between knowledge, information sources, and family support with pregnant women’s compliance in the Triple Elimination programme. A cross-sectional study was conducted among 132 pregnant women attending health facilities in Arcamanik Sub-district, Bandung City. Participants were selected using purposive sampling, and data were collected using structured questionnaire. Univariate analyses described the frequency and distribution of variables, whilst bivariate analyses using Chi-squared and Mantel-Haenszel odds ratio (95% CI) assessed associations between knowledge, information sources, and family support with the pregnant women’s compliance. The results showed that most respondents had high knowledge (66.7%), adequate access to information (71.2%), and positive family support (67.4%), while 56.1% were compliant with the programme. Knowledge (OR [95% CI] = 10.99 [4.59–26.32], p<0.01), information sources (5.97 [2.57–13.87], p<0.01), and family support (15.66 [6.10–40.18], p<0.01) were all significantly associated with compliance, with family support being the strongest determinant. These findings highlight the importance of involving families in health education to strengthen pregnant women’s participation and improve the success of the Triple Elimination Programme.